The French Resistance - Lawson, Don (Wanderer Books, 1984)
Describes the French Resistance, the underground movement which through undetected acts of sabotage, intelligence gathering, and willingness to risk their lives, insured countless German defeats and strongly influenced the outcome of World War II.
Keywords: Geschichte; Weltkrieg (1939-1945); Guerrillas -- France -- Biography -- Juvenile literature; World War, 1939-1945 -- Underground movements -- France; World War, 1939-1945 -- Underground movements -- France -- Juvenile literature; Résistance; Frankreich; France -- History -- German occupation, 1940-1945; France -- History -- German occupation, 1940-1945 -- Juvenile literature; Biografie